Genetic Polymorphisms of FCRL3, NLRP3 and IL2 are Associated with the Risk of Head and Neck Cancer in a Chinese Population - Zhang Y; Sun D (Dove Medical Press, 2021)
Yuhao Zhang,1,2 Dawei Sun3 1Department of Otolaryngology Head and Neck Surgery, Shanxi Bethune Hospital, Shanxi Academy of Medical Sciences, Tongji Shanxi Hospital, Third Hospital of Shanxi Medical University, Taiyuan, 030032, People's Republic of China; 2Department of Otolaryngology Head and Neck Surgery, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People's Republic of China; 3Department of Thyroid Surgery, The Affiliated Hospital of Qingdao University, Qingdao, Shandong, 266000, People's Republic of ChinaCorrespondence: Dawei SunDepartment of Thyroid Surgery, The Affiliated Hospital of Qingdao University, #16 Jiangsu Road, Qingdao, Shandong, 266000, People's Republic of ChinaEmail sundawei18669@sina.comPurpose: This study aimed to evaluate the associations between immune-related gene (FCRL3, NLRP3 and IL2) polymorphisms and the risk of head and neck cancer (HNC).Methods: Six polymorphisms of FCRL3, NLRP3 and IL2 were genotyped in 400 HNC cases and 400 controls using a MassARRAY platform.Results: rs11264799-T was a protective variant against HNC risk, while rs7528684-G, rs35829419-A and rs6822844-T were all risk alleles for HNC (p < 0.05). rs11264799-TT was correlated with reduced HNC risk, while rs7528684-GG and rs6822844-TG were associated with an elevated risk of disease (p < 0.05). Moreover, rs11264799 was correlated with a declining risk of HNC in three genetic models (p < 0.05). In contrast, rs7528684 exhibited an elevated risk of HNC in recessive and additive models; rs35829419 and rs6822844 were associated with an increased risk of disease in dominant and additive models (p < 0.05). Finally, an interaction was observed between the above SNPs and drinking (p < 0.05).Conclusion: The results expand our knowledge on immune-related gene polymorphisms in HNC and provide clues for further functional study on the pathogenesis of HNC.Keywords: head and neck cancer, HNC, Fc receptor-like 3, FCRL3, NLR family pyrin domain containing 3, NLRP3, interleukin 2, IL2, genetic polymorphisms